Importance of Mycoplasma hominis in acute salpingitis assessed by culture and serological tests. Issue 3 (June 1985) - Lind, K; Kristensen, G B; Bollerup, A C; Ladehoff, P; Larsen, S; Marushak, A; Rasmussen, P; Rolschau, J; Skoven, I; Sørensen, T
Abstract : In 95 women with a provisional diagnosis of pelvic inflammatory disease, a final diagnosis of acute salpingitis was confirmed by laparoscopy in 46 and 10 had strong clinical evidence of acute salpingitis. The findings in the remaining 39 patients without signs of acute salpingitis by laparoscopy were used as a standard of reference. Criteria for the diagnosis of possible mycoplasmal salpingitis were tentatively defined as the isolation of Mycoplasma hominis from the cervix together with positive test results for M hominis antibodies (a titre of greater than or equal to 1/1280 or a change in titre, or both); these criteria were fulfilled in 12 patients with acute salpingitis. A positive correlation between mycoplasmal salpingitis and chlamydial salpingitis or gonococcal salpingitis, or both, was significant. Mycoplasmal salpingitis was not associated with any characteristic clinical feature different from those of patients with non-mycoplasmal salpingitis. Our findings do not support the view that M hominis is an important primary pathogen in acute salpingitis.